Peran Perfeksionisme terhadap Academic Burnout pada Mahasiswa Kedokteran: Pengujian Perfeksionisme Model 2 x 2 - Fadhlurrahman, Fakhri Rizky; Rahayuningsih, Tri; Anggreiny, Nila (INSAN Jurnal Psikologi dan Kesehatan Mental, 2024)
Medical students have a higher risk of academic burnout and perfectionism was found to play a role in this psychological syndrome. The 2 x 2 model of perfectionism proposes that two dimensions of perfectionism, perfectionistic strivings (PS) and perfectionistic concerns (PC), exist and interact at certain level within a person, forming four subtypes of perfectionism, pure PS, pure PC, mixed-perfectionist, and non-perfectionists. This research examines differences of academic burnout based on the four subtypes of perfectionism in medical students (n = 264). The results of simple effect analysis on factorial ANOVA results show academic burnout in medical students is significantly lower in pure PS than mixed-perfectionist and non-perfectionist, and significantly higher in pure PC than mixed-perfectionist and non-perfectionist, in line with the 2 x 2 model of perfectionism. This study shows that the 2 x 2 model of perfectionism is useful for understanding academic burnout in medical students.